Factors influencing participation in an Ebola vaccine trial among front-line workers in Guinea - Grantz, Kyra H.; Claudot, Pauline; Kambala, Micky; Kouyaté, Mariama; Soumah, Aboubacar; Boum, Yap; Juan-Giner, Aitana; Jemmy, Jean-Paul; Cummings, Derek A.T.; Grais, Rebecca F. (Vaccine, 2019)
Alongside the clinical aspects of the immunogenicity and safety trial of an Ebola vaccine deployed among front-line workers, a qualitative study was conducted to describe motivations behind individuals’ decisions to participate – or not to participate – in the study. In July and August 2015, focus group discussions and semi-structured individual interviews were conducted in Conakry, Guinea. Individuals were eligible for the qualitative study if they met the inclusion criteria of the immunogenicity and safety study irrespective of their participation. Surveys were also conducted among several institution and department heads of staff included in the study as well as vaccine trial staff members. Discussion and interview transcripts were analyzed using content thematic analysis. Interviews and focus groups were conducted among 110 persons, of whom about two-thirds (67%) participated in the vaccine trial. There was at least one group interview conducted at each participating trial site, along with numerous formal and informal interviews and conversations through the enrollment period. Participants were often motivated by a desire to save and protect themselves and others, contribute to scientific progress, or lead by example. Non-participants expressed concerns regarding the risk and costs of participation, particularly the fear of unknown side effects following vaccination, and distrust or fear of stigmatization. Despite the unique nature of the 2014–2015 Ebola outbreak, front-line workers employed much of the same logic when choosing to participate as in other clinical trials in similar settings. Special consideration should be given to addressing perceived inequity, misunderstanding, and mistrust among the target populations in future trials. Clinical trial registry number: This trial is registered with the Pan African Clinical Trials Registry, number PACTR201503001057193.